Clinical status and detection of periodontopathogens and Streptococcus mutans in children with high levels of supragingival biofilm - Sheila Cavalca Cortelli; José Roberto Cortelli; Davi Romero Aquino; Marinella Holzhausen; Gilson Cesar Nobre Franco; Fernando de Oliveira Costa; Daniel Fine (Sociedade Brasileira de Pesquisa Odontológica, 2009)
Knowledge about the presence of some important oral pathogens is an important step in better identifying children at risk for periodontal and/or caries diseases in later life. The purpose of this study was to detect the presence of Streptococcus mutans (Sm), Aggregatibacter actinomycetemcomitans (Aa), Campylobacter rectus (Cr), Porphyromonas gingivalis (Pg), Prevotella intermedia (Pi), and Tannerella forsythia (Tf) in gingival biofilm samples from 196 children, and to assess whether any of these pathogens are more associated with gingival inflammation extension and the Decayed/Missing/Filled teeth (DMFT/dmft) index. The subjects presented plaque index greater than 80% and were divided in 3 groups according to the bleeding index (BI): I) Low bleeding (< 30%), II) Medium bleeding (31 - 59%) and III) High bleeding (> 60%). The presence of each pathogen was determined by PCR. The prevalence of Sm was 71.9% and the mean dmft/DMFT was 6.68. The prevalence in low, medium and high bleeding groups was 43.5%, 34.5% and 46.7% for Aa; 43.5%, 37.9%, and 36.7% for Cr; 99.1%, 100%, and 96.7% for Pg; 56.5%, 56.9%, and 66.7% for Pi; and 58.3%, 60.3%, and 56.7% for Tf, respectively. Pg (99.0%) was the most prevalent periodontal pathogen detected followed by Tf (58.7%), Pi (58.2%), Aa (41.3%) and Cr (40.8%). Our study indicated that in this high plaque index population studied, a high prevalence of Sm and high mean DMFT were observed. In addition, the presence of Pi was associated with the presence of inflammation (P < 0.05) whereas Cr was associated with periodontal health (P < 0.05).